The influence of cutting parameter under sustainable machining approaches on surface roughness of AISI 4340 / Ahsana Aqilah Ahmad, Jaharah A. Ghani and Che Hassan Che Haron - Ahmad, Ahsana Aqilah; A. Ghani, Jaharah; Che Haron, Che Hassan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
This study presents the result of surface roughness (SR) during milling AISI 4340 under sustainable machining techniques of minimum quantity lubrication (MQL) and cryogenic using liquid nitrogen (LN2). Along with MQL, Treated Recycled Cooking Oil (TRCO) using waste Palm Oil is used to promote a greener cutting condition. Taguchi L9 orthogonal array and ANOVA are used to investigate the effect of cutting parameters (cutting speed, feed rate, depth of cut and width of cut) on the measured output value. Statically, in both conditions results show that cutting speed and feed rate are the parameters that affect the surface roughness. ANOVA analysis for MQL cutting found that feed rate contributed 87.39% of the output value. While in the cryogenic condition, cutting speed is the main factor that affects the SR value, representing 54.83%. At a lower cutting speed, the SR yield during MQL is lower compared to cryogenic conditions. At a higher cutting speed, the SR value in the cryogenic condition is better than that in MQL condition. However, when the feed rate increases, the SR value is almost similar in both conditions. This finding shows that using this experimental condition with TRCO can improve the SR value even at a higher cutting speed.